Intrusions of sediment laden rivers into density stratified water columns could be an unrecognized source of mixing in many lakes and coastal oceans. Issue 5 (11th April 2022) - Lu, George; Wells, Mathew; van Strygen, Ian; Hecky, Robert. E.
Abstract: When a sediment laden river flows into a stratified water body, the water mass can either intrude as an overflow, interflow or underflow, depending upon the density contrast. Different modes of sediment driven convection occur in each case. For the case of overflows, convective sedimentation occurs beneath the plume, whereby sediment rich plumes rapidly transport fine materials to depth. If underflow of dense sediment laden waters initially occurs, then after sediment has been deposited, the light interstitial material can subsequently loft and potentially mixes the entire water column. For an interflow, both lofting and sediment driven convection can occur above and below the pycnocline. All of these different regimes can be described in terms of two dimensionless parameters: namely R S = Δ ρ S /Δ ρ C and R A = Δ ρ A /Δ ρ C, where Δ ρ A is the density contrast between the upper layer and the river inflow (due to just salinity or temperature differences), Δ ρ C is the density contrast due to sediment between river and upper‐layer, and Δ ρ S is the density contrast between upper and lower layers (due to just salinity or temperature differences). Laboratory experiments were used to describe the vigour of convection in terms of these dimensionless parameters, which then allows behaviour of various inflows to be predicted. In most cases the convective velocities observed were an order of magnitude faster than Stokes settling velocities. These observations are also applied to predict how a turbidity current could lead to lofting and possible overturn of the stratification of Lake Kivu, a large meromictic lake between Rwanda and the Democratic Republic of the Congo.